Achieving large super-elasticity through changing relative easiness of deformation modes in Ti-Nb-Mo alloy by ultra-grain refinement. Issue 5 (4th May 2021) - Zhang, Bingjie; Huang, Mingda; Chong, Yan; Mao, Wenqi; Gong, Wu; Zheng, Ruixiao; Bai, Yu; Wang, Dong; Sun, Qiaoyan; Wang, Yunzhi; Tsuji, Nobuhiro
Abstract : Large super-elasticity approaching its theoretically expected value was achieved in Ti-13.3Nb-4.6Mo alloy having an ultrafine-grained β-phase. In-situ synchrotron radiation X-ray diffraction analysis revealed that the dominant yielding mechanism changed from dislocation slip to martensitic transformation by decreasing the β-grain size down to sub-micrometer. Different grain size dependence of the critical stress to initiate dislocation slip and martensitic transformation, which was reflected by the transition of yielding behavior, was considered to be the main reason for the large super-elasticity in the ultrafine-grained specimen. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: The present study clarified that ultra-grain refinement down to sub-mirometer scale made dislocation slips more difficult than martensitic transformation, leading to an excellent super-elasticity close to the theoretical limit in the β-Ti alloy.